In the line of the sketch, as in the linearity of the parade: appreciations about A 1913 carnival revelry and the Ameno Resedá ranch (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2023)
The book A Folia Carnavalesca de 1913 e o rancho Ameno Resedá is the result of research by Madson Oliveira, Adjunct Professor of the Performing Arts – Clothing course at the School of Fine Arts at UFRJ. There is already on the beautiful cover the index of this linear reading of the carnival event: costume sketches follow one another, forming a parade. The reader is led from a panoramic view of the carnival, to a focus on the social division within the carnival event from the 19th to the 20th century: The trump card of the research is its documental and investigative character, advancing beyond the contribution of previous researchers and journalists who pored over the history of this ranch.
Keywords: carnival; parade; file; linearity